Puesta en valor de una escuela patrimonial en zona de alto riesgo sísmico: un caso de estudio - Maldonado, N. G.; Martín, P.; Maldonado, I.; Calderón, F. (Revista ALCONPAT, 2014)
The Mitre School is a monumental building enabled in 1906 using fired ceramic masonrywithout tie-reinforcement. During its service life it has suffered damages from impulsiveearthquakes in Mendoza, Argentina, as well as from changes in the materials and lack ofmaintenance. The methodology of study included the following stages: a detailed inspection,emergency decisions, analysis of conservation state of the building, as well as the diagnosisand rehabilitation alternatives. With the data from the field and laboratory tests, the buildingwas modeled by using finite elements. The advantages of the use of concrete in therehabilitation include the lowest cost and the best structural performance according torehabilitation standards in force; nonetheless, from the standpoint of heritage, thecombination of steel structures, that do not interfere with the original factory, and therehabilitation of reinforced concrete foundations are preferred.Keywords: heritage, safety, seismic resistant, enhancement.